Using of Thermal Analysis in the Industrial Practice - Consumption Reduction of Grain-Refinement Master Alloy and Optimization of Computer Simulation Results - Grzincic, Marko; Djurdjevic, Mile; Dirnberger, Florian (Manufacturing Technology Journal, 2013)
The solidification process of a metal or alloy is accompanied by the evolution of heat the magnitude of which depends on the various phases that form during the solidification. Recorded temperature-time data can yield quantitative information about the alloy solidification process. Such a plot is called a cooling curve and the general name given to the technique is thermal analysis. The cooling curve serves as a "finger print" of the solidification process and can be used to predict the structure of the test sample and consequently the actual casting. The aim of this paper is to show the ability of the thermal analysis technique in order to predict some of the key solidification parameters, which can be used to monitor and improve the quality of the casting. In addition, some of the results collected from the cooling curve can be used as an input data in existing software packages in order to improve their accuracy.
Keywords: thermal analysis; cooling curve analysis; grain-refinement; master alloy AlTi5B1; dendrite coherency point